Activation of the Keap1/Nrf2 pathway suppresses mitochondrial dysfunction, oxidative stress, and motor phenotypes in C9orf72 ALS/FTD models. - Au, W.H.; Miller-Fleming, L.; Sanchez-Martinez, A.; Lee, J.A.; Twyning, M.J.; Prag, H.A.; Raik, L.; Allen, S.P.; Shaw, P.J.; Ferraiuolo, L.; Mortiboys, H.; Whitworth, A.J. (Life science alliance, 2024)
Mitochondrial dysfunction is a common feature of C9orf72 amyotrophic lateral sclerosis/frontotemporal dementia (ALS/FTD); however, it remains unclear whether this is a cause or consequence of the pathogenic process. Analysing multiple aspects of mitochondrial biology across several Drosophila models of C9orf72-ALS/FTD, we found morphology, oxidative stress, and mitophagy are commonly affected, which correlated with progressive loss of locomotor performance. Notably, only genetic manipulations that reversed the oxidative stress levels were also able to rescue C9orf72 locomotor deficits, supporting a causative link between mitochondrial dysfunction, oxidative stress, and behavioural phenotypes. Targeting the key antioxidant Keap1/Nrf2 pathway, we found that genetic reduction of Keap1 or pharmacological inhibition by dimethyl fumarate significantly rescued the C9orf72-related oxidative stress and motor deficits. Finally, mitochondrial ROS levels were also elevated in C9orf72 patient-derived iNeurons and were effectively suppressed by dimethyl fumarate treatment. These results indicate that mitochondrial oxidative stress is an important mechanistic contributor to C9orf72 pathogenesis, affecting multiple aspects of mitochondrial function and turnover. Targeting the Keap1/Nrf2 signalling pathway to combat oxidative stress represents a therapeutic strategy for C9orf72-related ALS/FTD.